Characterization of Progenies from Intergeneric Hybridization Between Oryza sativa L. and Porteresia coarctata (Roxb.) Tateoka (Plant Tissue Culture and Biotechnology, 2017)
Porteresia coarctata (Roxb.) Tateoka is an endemic halophyte growing all over the coastal belt of Bangladesh, propagating through rhizomes and setting a few ricelike grains. So exploiting the genetic potential of this wild rice as salt tolerant donor in possible wide crosses with rice (2n = 24) could be useful. We attempted intergeneric hybridization between Oryza sativa L. and P. coarctata. The survival rate of hybrid progenies in embryo culture was low but among them 2 hybrid plants were successfully matured from the intergeneric cross between the cultivated induced tetraploid of rice, Latisail (2n = 4x = 48) and P. coarctata (2n = 48). The hybrid plants could be successfully established in soil and were not like either of the parents in morphology although some of their features were similar to their maternal parent, Latisail (4x). Both of the hybrids were investigated through physiological analysis under salinity stress and molecular analyses with rice specific SSR markers. Molecular analysis of the F1 DNA with only 3 SSR markers, RM581, RM20224 and RM25271, out of 36 others tested, showed bands specific to both of the parents, while all had common bands with the maternal parent. Dendrogram analysis of the hybrids with the 36 SSR markers, show that P. coarctata forms a different clade and is clearly separated from Latisail and the hybrids. The putative hybrids however made a subgroup with Latisail. These observations could be possibly explained if chromosome loss of the paternal parent had occurred or may be it was a pleotropic effect of intergeneric hybridization. Physiological screening of the hybrid progenies at the F2 generation in seedling stage showed better result in leaf damage score (LDS) and salinity tolerance than their maternal parent Latisail (4x) at 150 mM salt stress for 10 days. F2 plants from one of the hybrid plants (H‐2) showed better performance but there was a large variation in response from each of the individual progenies. So, it is likely that some of the salt tolerant characteristics of the pollen parent might have been transferred to the recipient Latisail (4x). For introgression of better salt tolerant loci from P. coarctata, more wide hybrids will need to be produced and repeatedly crossed with P. coarctata.Plant Tissue Cult. & Biotech. 27(1): 63-76, 2017 (June)